Cloud-Radiation Feedback: Boundary Layer Cloud Microphysical Properties and Processes - Paul Lawson (Arctic Data Center)
This data set includes Surface Heat Budget of the Arctic (SHEBA) cloud microphysical data collected onboard the National Center for Atmospheric Research (NCAR) C-130 aircraft. This work focused on improving the quality of algorithms used to process in situ measurements collected during First International Satellite Cloud Climatology Project (ISCCP) Regional Experiment, Arctic Cloud Experiment (SHEBA/FIRE, ACE) and applying the results to the analysis of five case studies. Such research was deemed valuable as a result of weaknesses and inconsistencies in the existing C-130 data set that were pointed out in a SHEBA workshop held in 2000. Data has been reprocessed by SPEC, Inc. to improve quality and add value to the measurements. Investigators selected five research days that were considered to be high priority by the SHEBA science team: 4 May, 8 July, 18 July, 28 July, and 29 July of 1998. The data were originally distributed on a CD-ROM. The data are now available as a single tar.gz file that contains the contents of the CD-ROM.